Hair Transplant Follicular Unit Extraction Technique as a Current Treatment Option for Androgenetic Alopecia - Gardenia Akhyar; Nagara, Adianto Jaya (HM Publisher, 2024)
The therapy for androgenetic alopecia currently varies, and there is no generally efficacious form of treatment. Despite receiving therapy, a portion of individuals with alopecia still do not achieve the anticipated hair regrowth outcomes. The absence of efficacious medical intervention typically necessitates the exploration of alternative therapy modalities. A significant number of patients who do not get satisfactory results from medical treatment explore other therapeutic approaches, such as hair transplantation. Advancements in hair transplantation procedures have seen substantial progress since the 1960s. Men frequently seek hair transplantation, making it a popular cosmetic treatment. Over 11,000 operations took place in the United States in 2014. Commonly practiced contemporary hair transplant procedures include follicular unit transplantation (FUT) and follicular unit extraction (FUE). The FUE technique is gaining popularity due to its non-invasive nature, quicker recovery time, reduced post-operative discomfort, and fewer surgical scars, in contrast to the FUT approach.